Tuberculosis presenting as Lung mass - Raghu, Srikanti; Srikanth, Juvva Kishan; Pulivarthi, Surya Kiran (International Journal of Medical Research and Review, 2015)
Pulmonary tuberculosis remains one of the major health problem through out the world. Pulmonary Tuberculosis has variable presentation, may present as a mass lesion. Here we are reporting a rare case presenting with dry cough with intermittent fever since 1 month,significant weight loss and one bout of hemoptysis 2 days back . A mass lesion noted in the right lower zone on chest x- ray and confirmed by Computed Tomography (CT) scan. Ultra sound aided Fine Needle Aspiration Cytology (FNAC) confirmed as tuberculosis.